One Dimensional Motion with ICT Based Learning: Improving the Physics Teacher Candidates’ Science Process Skills and Attitudes - Nuryantini, Ade Yeti; Mahen, Ea Cahya Septia (Universitas Islam Negeri Raden Intan Lampung, Indonesia, 2018)
Education nowadays is demanded to produce students who have beneficial skills of the 21st century in dealing with problems in the era of information and digital technology. Therefore, it is necessary to change the emphasis of learning patterns. In this paper, the results of the application of 21st-century skills in learning Basic Physics 1 in the Physics Education Study Program, UIN Sunan Gunung Djati Bandung using a scientific approach is presented. Learning activities were conducted based on low budget materials and ICT in the form of tracker software. The results showed that students were skilled in using tracker (90%), had science processing skills (excellent 5.2%, good 74.0%, and fair 20.8%), and fostered curiosity (92.0%), careful attitude (92.2%), caring for the environment (73.0%), honest (93.0%), and cooperative (97.0%)